(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article aims to argue that the category of character has expired and to postulate the alternative category of Figure in contemporary theater. The category of character is linked to the mimetic or figurative representation of the world, which makes the character inoperative in postdramatic or postrepresentational theaters of current times. The article follows in detail the alternatives that Jean-Pierre Sarrazac offered at the time of the character-figure, the character-creature and even the in-character as rescue strategies for the category, to ratify its crisis and its replacement by the notion of Figure in current theater.